Acordos de pesca na Região do Aritapera: percepções de sua importância como ferramenta de gestão da pesca na Região do Baixo Amazonas - ALMEIDA, Andréia Abreu de (Universidade Federal do Oeste do Pará, 2021)
The objective of this study is to evaluate the effectiveness of management measures for fisheries agreements in the Aritapera region, Santarém-PA (Pará / Brazil). It deals with fisheries agreements as a participatory management tool, making an analysis in relation to their implementation. The dynamics of fishing in these communities and their social actors are described in summary. These agreements arose from the pressure exerted on the communal lakes of floodplain, from the decade of the 70, where the riverside communities began to restrict the access to these environments. One of the main legal instruments for fisheries control used as a participatory management tool, as well as promising in increasing and maintaining fish stocks. It is necessary to evaluate this management tool as a support to obtain results on the efficiency of these agreements. The agreements of the Aritapera region in the first moment were regularized by means of ordinances and later recognized by means of Normative Instruction of Ibama n ° 11, of October 14, 2004. In the second moment, from the need of land regularization, INCRA in partnership with IPAM, created the Aritapera Agro-Extractive Settlement Project (PAE), making a total of 14 communities that had their fishing agreements introduced into the Plan of Use of the PAE by inserting them into a fishing chapter. The communities selected for this research were: Ilha de São Miguel, Água Preta, Boca de Cima and Cabeça D'ounca. The main source of income of these communities is fishing that occurs all year long and agriculture during the drought in the Amazon, the main environments used for fishing are community lakes, adapting their techniques and fishing gear according to rise and fall of the waters, it is made use of the crockery every year. Among the communities studied, the oldest fishing agreements are from the Ilha de São Miguel and Água Preta communities dating back to the 1980s and 1990s, respectively, Boca de Cima and Cabeça D'ounca communities had no formalized agreements and only came to have after the Utilization Plan (PU). Fisheries conflicts were observed in all the communities studied, with the highest citation in the Água Preta community. The greatest difficulty found in the implementation of the agreements is due to the lack of respect for the rules of the current agreement and due to the low state performance in the absence of inspections in these communities.